A comparative study of the dentate gyrus in hippocampal sclerosis in epilepsy and dementia. Issue 2 (February 2014) - Bandopadhyay, R.; Liu, J. Y. W.; Sisodiya, S. M.; Thom, M.
<x xml:space="preserve">Abstract</x> Aims: Hippocampal sclerosis (HS) is long‐recognized in association with epilepsy (HSE) and more recently in the context of cognitive decline or dementia in the elderly (HSD), in some cases as a component of neurodegenerative diseases, including Alzheimer's disease (AD) and fronto‐temporal lobe dementia (FTLD). There is an increased risk of seizures in AD and spontaneous epileptiform discharges in the dentate gyrus of transgenic AD models; epilepsy can be associated with an age‐accelerated increase in AD‐type pathology and cognitive decline. The convergence between these disease processes could be related to hippocampal pathology. HSE typically shows re‐organization of both excitatory and inhibitory neuronal networks in the dentate gyrus, and is considered to be relevant to hippocampal excitability. We sought to compare the pathology of HSE and HSD, focusing on re‐organization in the dentate gyrus. Methods: In nine post mortem cases with HSE and bilateral damage, 18 HSD and 11 controls we carried out immunostaining for mossy fibres (dynorphin), and interneuronal networks (NPY, calbindin and calretinin) on sections from the mid‐hippocampal body. Fibre sprouting (FS) or loss of expression in the dentate gyrus was semi‐quantitatively graded from grade 0 (normal) to grade 3 (marked alteration). Results: Significantly more re‐organization was seen with all four markers in the HSE than HSD group (P < 0.01). Mild alterations were noted in HSD group with dynorphin (FS in 3 cases), calretinin (FS in 6 cases), NPY (FS in 11 cases) and calbindin (loss in 10 cases). In eight HSD cases, alteration was seen with more than one antibody but in no cases were the highest grades seen. We also noted NPY and, to a lesser extent, calretinin labelling of Hirano bodies in CA1 of AD cases and some older controls, but not in HSE. Conclusion: Reorganization of excitatory and inhibitory networks in the dentate gyrus is more typical of HSE. Subtle alterations in HSD may be a result of increased hippocampal excitability, including unrecognized seizure activity. An unexpected finding was the identification of NPY‐positive Hirano bodies in HSD but not HSE, which may be a consequence of the relative vulnerabilities of interneurons in these conditions.